Evaluación de campañas publicitarias mediante modelos econométricos: el caso de la campaña de ahorro de energía eléctrica 1995-1998 - Simabuko, Luis (2001)
Economic theory indicates that energy consumption is a demand derived from the consumption of electrical appliances from which short-term and long-term demand can be derived. From these two approximations two basic models are derived to estimate the electric power demand of the families.